2018
DOI: 10.3389/fbioe.2018.00163
|View full text |Cite
|
Sign up to set email alerts
|

Make It Simple: (SR-A1+TLR7) Macrophage Targeted NANOarchaeosomes

Abstract: Hyperhalophilic archaebacteria exclusively produce sn2,3 diphytanylglycerol diether archaeolipids, unique structures absent in bacteria and eukaryotes. Nanovesicles made of archaeolipids known as nanoarchaeosomes (nanoARC), possess highly stable bilayers, some of them displaying specific targeting ability. Here we hypothesize that nanoARC made from Halorubrum tebenquichense archaebacteria, may constitute efficient carriers for the TLR7 agonist imiquimod (IMQ). NanoARC-IMQ takes advantage of the intense interac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 59 publications
1
9
0
Order By: Relevance
“…Encapsulation of drugs is another useful pharmaceutical strategy for topical CL treatment as it can offer enhanced permeation of the active drug, immunomodulatory effects, and macrophage-targeted delivery (Moreno et al, 2014), (Parra et al, 2018). Considering the complex cellular and tissue interactions of these particles, the evaluation of skin penetration requires extensive model optimization and combinations of sensitive imaging and detection methods such as Raman spectroscopy, X-ray microscopy, and flow cytometry in addition to the Franz diffusion cell assays (Vogt et al, 2014).…”
Section: Pharmacokinetics and Pharmaceuticsmentioning
confidence: 99%
“…Encapsulation of drugs is another useful pharmaceutical strategy for topical CL treatment as it can offer enhanced permeation of the active drug, immunomodulatory effects, and macrophage-targeted delivery (Moreno et al, 2014), (Parra et al, 2018). Considering the complex cellular and tissue interactions of these particles, the evaluation of skin penetration requires extensive model optimization and combinations of sensitive imaging and detection methods such as Raman spectroscopy, X-ray microscopy, and flow cytometry in addition to the Franz diffusion cell assays (Vogt et al, 2014).…”
Section: Pharmacokinetics and Pharmaceuticsmentioning
confidence: 99%
“…DPPC has been well researched and employed for developing liposomal inhalation suspensions for targeted lung delivery and interventions including penetration of biofilms and uptake into macrophages (Chimote and Banerjee, 2010;Zhang et al, 2018). In addition, endogenous lung surfactant inspired strategies including phospholipid based nanovesicle aerosols (Joshi et al, 2015;Altube et al, 2017;Parra et al, 2018) have been reported as pulmonary compatible and efficient drug delivery platforms.…”
Section: The Hypothesis and The Discussionmentioning
confidence: 99%
“…The combination of such unique biophysical and pharmacodynamics features of nanoARC bilayers, was recently exploited to trap difficult to dissolve in water drugs, such as the immunomodulator imiquimod. 59 Despite of the AZ: lipid w:w ratios of nanoARC-AZ (0.28) (vs (0.20) from nanoL-AZ nanoliposomes made of ordinary phospholipids used as a control) were comparable and in the order of those previously reported for other AZ vesicular formulations (~0.24 27 and ~0.23 60 ), the interaction between AZ and nanoARC bilayers was unique, and different from that occurring within nanoliposomes, where AZ remained dissolved/precipitated within the aqueous space. The  potential values, together with the structural data provided by GP, FA and SAXS, showed that AZ associated to nanoARC bilayers consisted of a combination of electrostatic interaction between negatively charged nanoARC surface and the two tertiary amines of ~ 8.7 and ~ 9.3 pKa from dicationic AZ 61 with trapping within the interface and the inner most methyl groups.…”
Section: Discussionmentioning
confidence: 99%
“…PGP-Me containing nanoARC, therefore, is naturally targeted to cells expressing SRA1. The combination of such unique biophysical and pharmacodynamic features of nanoARC bilayers was recently exploited to trap difficult-to-dissolve-in-water drugs, such as the immunomodulator imiquimod …”
Section: Discussionmentioning
confidence: 99%